2021
DOI: 10.1002/pssa.202100228
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Photoresponsive Photodetector Based on Graphene/SnS2 van der Waals Heterostructure

Abstract: SnS2 exhibits a high absorbance coefficient and strong photoconductive properties in ultraviolet–visible regions, making it a promising photodetector with excellent photoelectric performance. The characteristic of a large yield of photocarriers in SnS2 with the high mobility of graphene is combined and a vertical graphene/SnS2 van der Waals heterostructure photodetector is fabricated, which can obtain effective electron–hole pairs separation under the built‐in electric field, thus having a high photoresponse. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…With the increase of laser power density from 0 to 4.4 mW cm −2 , the In 2 Se 3 &WSe 2 heterotransistor gradually exhibits a change in polarity from P-type to anti-ambipolar, and the I peak value shifts from 0 to 4.3 nA and the V peak value shifts from −7 to −5.67 V. So, it can be concluded that the photogenerated carriers drift under the effect of the built-in electric field in this heterotransistor, and the accumulation of such carriers can lead to the V th shifting of this heterotransistor, thus triggering the phenomenon that the charge polarity of the In 2 Se 3 &WSe 2 heterotransistor changes from P-type to antiambipolar. [39][40][41][42][43][44][45][46][47][48][49][50][51][52] The principle was further analysed by the energy band structure. Kelvin probe force microscopy (KPFM) is employed to unveil the trend of the Fermi level shift of In 2 Se 3 and WSe 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…With the increase of laser power density from 0 to 4.4 mW cm −2 , the In 2 Se 3 &WSe 2 heterotransistor gradually exhibits a change in polarity from P-type to anti-ambipolar, and the I peak value shifts from 0 to 4.3 nA and the V peak value shifts from −7 to −5.67 V. So, it can be concluded that the photogenerated carriers drift under the effect of the built-in electric field in this heterotransistor, and the accumulation of such carriers can lead to the V th shifting of this heterotransistor, thus triggering the phenomenon that the charge polarity of the In 2 Se 3 &WSe 2 heterotransistor changes from P-type to antiambipolar. [39][40][41][42][43][44][45][46][47][48][49][50][51][52] The principle was further analysed by the energy band structure. Kelvin probe force microscopy (KPFM) is employed to unveil the trend of the Fermi level shift of In 2 Se 3 and WSe 2 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The phototransistor achieves a maximum responsivity of 1301 A/W, which is significantly greater than the responsivity of other similar 2D-material-based FETs, , as shown in Table . Such high responsivity can be credited to high light absorption of a certain thickness of SnS 2 and the good contact between SnS 2 and the van der Waals electrodes. Moreover, the existence of trap centers in SnS 2 causes holes to be trapped, extending their lifetime, and preventing the recombination of electron–hole pairs, producing a high response.…”
Section: Resultsmentioning
confidence: 99%
“…This effect, known as the photogating effect, is a significant contributor to the high responsivity. Additionally, the large specific surface area and water-assisted and oxygen-assisted mechanisms all contribute significantly to the improvement of the response …”
Section: Resultsmentioning
confidence: 99%
“…[295] An integration of Gr with very high μ and SnS2 with a large yield of photocarriers can make a vertical Gr/SnS2 vdW heterostructure PD with very high performance. Taking this fact as a cue, a Gr/SnS2 PD [296] was fabricated (SiO2/Si substrate) that showed an ultrahigh R of 6.35 × 10 5 A/W (at 365 nm light illumination), which is substantially higher than that of single Gr or SnS2. What's more, the PD demonstrated a high EQE of 2.15 × 10 8 % and a D * of 3.68 × 10 11 .…”
Section: High Performance Pds With 2d/2d Heterostructuresmentioning
confidence: 99%